Easter bunny murder ebook - Meier, Leslie (Lucy Stone, 2013)
Spring has sprung in Tinker's Cove, and Lucy Stone has a mile-long to-do list. From painting eggs with her grandson, to preparing the perfect Easter feast, to reviving her garden after a long, cold winter, she hardly has time to search for a killer with a deadly case of spring fever. . . Lucy has always loved covering the annual Easter egg hunt for the Pennysaver. Hosted by elderly socialite Vivian Van Vorst at Pine Point, her luxurious oceanfront estate, it's a swanky event where the grown-ups sip cocktails while their children search for eggs that are as likely to contain savings bonds as they are jelly beans. But when Lucy arrives with her three-year-old grandson, VV's normally welcoming gates are locked, and a man dressed as the Easter Bunny emerges only to drop dead moments later. . . Lucy discovers that the victim is Van Vorst Duff, VV's grandson, and soon learns that not all is as it seems at idyllic Pine Point, where the champagne and caviar seem to be running dry. Always a social butterfly, VV has been skipping lunch dates with friends, and her much-needed donations to local charities have stopped with no explanation. Maybe she's going senile, or maybe her heirs are getting a little too anxious to take over her estate. . . As Lucy gathers a basketful of suspects, she's convinced that someone's been hunting for a lot more than eggs. And she'll have to chase the truth down a rabbit hole before the killer claims another victim. . . "Reading a new Leslie Meier mystery is like catching up with a dear old friend." —Kate Carlisle, New York Times bestselling author